Microcell Planning Analysis Using Cell Splitting Method In 4G LTE Network - Yuhanef , Afrizal; Zurnawita, Zurnawita; Berliana Syafira , Gerin; Septima, Uzma; Setiawan, Herry (Politeknik Ganesha Medan, 2024)
As the growth of technology and telecommunication network, demands of mobile technology is also raised. The quality of the network will decrease by the insufficient number of network and cell to support the growth of user, and the scope of e-Node B is not optimal. The method of cell splitting can be used to solve the problem, this method splitting macro cell network become smaller size of cell with scoping area of each without interruption. The planning of new site as microcell implemented in area of Flamboyan Baru using XL operator. As the count gained, 1 site microcell and 2 cell with the antenna of 18,5 meters and power of 38 dBm, cell splitting method could increase network quality and improve the average number of parameter RSRP, SINR, and throughput, also proving that the implementation of cell splitting in microcell could escalate the quality of LTE network, the improvement of network quality in SINR parameter with average number of 24,23 dB with category of very good, RSRP parameter with average number of -94,28 dBm with category good, and the average number of throughput reach 63.094,91 kbps with category very good.